Twenty five year mortality and air pollution: results from the French PAARC survey. Issue 7 (16th June 2005) - Filleul, L; Rondeau, V; Vandentorren, S; Le Moual, N; Cantagrel, A; Annesi-Maesano, I; Charpin, D; Declercq, C; Neukirch, F; Paris, C; Vervloet, D; Brochard, P; et al.
Abstract : Aims and Methods: Long term effects of air pollution on mortality were studied in 14 284 adults who resided in 24 areas from seven French cities when enrolled in the PAARC survey (air pollution and chronic respiratory diseases) in 1974. Daily measurements of sulphur dioxide, total suspended particles, black smoke, nitrogen dioxide, and nitric oxide were made in 24 areas for three years (1974–76). Cox proportional hazards models controlling for individual confounders (smoking, educational level, body mass index, occupational exposure) were applied, and frailty models used to take into account spatial correlation. Indicators of air pollution were the mean concentration. Results: Models were run before and after exclusion of six area monitors influenced by local traffic (NO/NO2 >3 in ppb). After exclusion of these areas, analyses showed that adjusted risk ratios (95% CI) for TSP, BS, NO2, and NO for non-accidental mortality were 1.05 (1.02 to 1.08), 1.07 (1.03 to 1.10), 1.14 (1.03 to 1.25), and 1.11 (1.05 to 1.17) for 10 μg/m 3 respectively. Consistent patterns for lung cancer and cardiopulmonary causes were observed. Conclusions: Urban air pollution assessed in the 1970s was associated with increased mortality over 25 years in France.